Analysis of Endoplasmic Reticulum Stress-Associated Proteins As Prognostic Markers In Breast Cancer - Shreya, Smriti; Pandey, Shweta; Ghosh, Debasish Kumar; Puneet; Prasad, Shyam Babu; Grosset, Christophe F.; Jain, Buddhi Prakash (Current Genomics, 2026)
<span class=
Keywords: unfolded protein response